Cefiderocol Resistance Conferred by Plasmid-Located Ferric Citrate Transport System in KPC-Producing Klebsiella pneumoniae - Riccardo Polani; Alice De Francesco; Dario Tomolillo; Irene Artuso; Michele Equestre; Rita Trirocco; Gabriele Arcari; Guido Antonelli; Laura Villa; Gianni Prosseda; Paolo Visca; Alessandra Carattoli (Emerging Infectious Diseases)
Cefiderocol (FDC), a siderophore-cephalosporin conjugate, is the newest option for treating infection with carbapenem-resistant gram-negative bacteria. We identified a novel mechanism contributing to decreased FDC susceptibility in Klebsiella pneumoniae clinical isolates. The mechanism involves 2 coresident plasmids: pKpQIL, carrying variants of blaKPC carbapenemase gene, and pKPN, carrying the ferric citrate transport (FEC) system. We observed increasing FDC MICs in an Escherichia coli model system carrying different natural pKpQIL plasmids, encoding different K. pneumoniae carbapenemase (KPC) variants, in combination with a conjugative low copy number vector carrying the fec gene cluster from pKPN. We observed transcriptional repression of fiu, cirA, fepA, and fhuA siderophore receptor genes in blaKPC–fec–E. coli cells treated with ferric citrate. Screening of 27,793 K. pneumoniae whole-genome sequences revealed that the fec cluster occurs frequently in some globally distributed different KPC-producing K. pneumoniae clones (sequence types 258, 14, 45, and 512), contributing to reduced FDC susceptibility.